EFFECT OF GNRH AGONIST AT DIFFERENT STAGES OF THE PGF2°" INDUCED ESTROUS CYCLE IN REPEAT BREEDER COWS - KRISHNAKUMAR, K; CHANDRAHASAN, C (The Indian Journal of Animal Reproduction, 2023)
Forty repeat breeder cows were randomly allotted into four groups and were induced to estrus with 25mg of PGF 2alpha "’, intramuscularly on day 10 of the estrous cycle. After estrus induction, group I was not given any treatment. Cows of group 11, 111 and IV were treated with 20μg of GnRH agonist, intramuscularly at 48 and 72 h after PGF 2alpha administration and day 5 post insemination respectively. Breeding was done with good quality frozen semen for all the groups at 72 and 96 h after PGF2" administration. The time taken forthe onset of estrus and duration of estrus in group II was shorter (P<0.01) than the other groups. The incidence of weak estrus was significantly higher in group II while the incidence of intense and intermediate estrus was significanUy higher in group Ill when compared with other groups. The group IV had significantly longer oestrous cycle length (P<0.01) than the other groups. The serum progesterone concentration did not differ significantly (P>0.05) on day O in any of the groups, but was significantly higher (P<0.05) in group II at 72 h after PGF2" injection, In group Ill on day 5, and in group IV on day 10 and 16 post insemination. The conception rate in the first service was higher in group Ill, the second service and overall conception rate was higher in group IV. It can be inferred from the present study that PGF 2.,. synchronized estrus combined with GnRH 72h after PGF2u administration and on day 5 post-insemination were found to have achieved fairly a good overall conception rate in repeat breeder cows.